Thomas goes fishing (New York : Random House, 2005)
Envious of the children who are fishing in the river near the railroad tracks, Thomas the tank engine finds a way to enjoy the same activity.
Keywords: Railroads -- Trains -- Fiction; Fishing -- Fiction